Cell-specific occupancy dynamics between the pioneer-like factor Opa/ZIC and Ocelliless/OTX regulate early head development in embryos - Fenelon, Kelli D.; Gao, Fan; Borad, Priyanshi; Abbasi, Shiva; Pachter, Lior; Koromila, Theodora (Frontiers in Cell and Developmental Biology, 2023)
During development, embryonic patterning systems direct a set of initially uncommitted pluripotent cells to differentiate into a variety of cell types and tissues. A core network of transcription factors, such as Zelda/POU5F1, Odd-paired (Opa)/ZIC3 and Ocelliless (Oc)/OTX2, are conserved across animals. While Opa is essential for a second wave of zygotic activation after Zelda, it is unclear whether Opa drives head cell specification, in the Drosophila embryo. Our hypothesis is that Opa and Oc are interacting with distinct cis-regulatory regions for shaping cell fates in the embryonic head. Super-resolution microscopy and meta-analysis of single-cell RNAseq datasets show that opa’s and oc’s overlapping expression domains are dynamic in the head region, with both factors being simultaneously transcribed at the blastula stage. Additionally, analysis of single-embryo RNAseq data reveals a subgroup of Opa-bound genes to be Opa-independent in the cellularized embryo. Interrogation of these genes against Oc ChIPseq combined with in situ data, suggests that Opa is competing with Oc for the regulation of a subgroup of genes later in gastrulation. Specifically, we find that Oc binds to late, head-specific enhancers independently and activates them in a head-specific wave of zygotic transcription, suggesting distinct roles for Oc in the blastula and gastrula stages.